Applicazioni tecnico metodologiche per il miglioramento della performance riproduttiva nel cane di allevamento - BASSU, Giovanna Maria (Università degli studi di Sassari, 2017)
Breeders often complain about a decreased fertility and veterinarians are more and more requested to solve fertility problems.In this study 5 breeds of dogs were selected on the basis of an infertility anamnesis. Newfoundland, English Bulldog, Hold English Mastiff, Great Dane and Dogue de Bordeaux. The purpose of this research was to determine the correlation between various fertility parameters and try to improve the production. There was no relation between parity and breeds in our population. In this study, there were more natural covers in great danes as compared to other breeds. English bulldogs and Old English Mastiffs in particular had significantly less natural breeding. There were significantly more positive pregnancy diagnoses in both primiparous and multiparous bitches in all breeds but in the great danes. This suggests a reduced fertility in that breed. Considering the number of puppies produced by a particular tecnic of insemination there is an effect only in Great Dane. In that breed, it seems that natual breeding is more efficient than the Artificial Insemination. A significant effect of the breed on the type of delivery was demonstrated (more c-sections in Bulldogs and Mastiffs, more natural deliveries in Newfoundland and Dogues de Bordeaux and no difference in Great Danes). Primiparous were not less likely to give birth naturally than multiparous bitches. Perpetuating artificial reproduction in dogs that, under natural conditions, could never contribute to the genetic pool, the low fertility in some bloodlines is probably explained by wrong breeder selection.